Effect of Different Die Materials on the Marginal Fit of CAD/ CAM crowns pre and pos -cementation - Sara AbdulBasit Turky AL-Bayat BSc1, Amal Abudl Latif MSc1, Abdulla M.W. Al-Shamma2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Theobjective of this in vitro study was to evaluate the vertical marginalgap pre and post-cementation ofIPS e.Max CAD crowns constructed using different die materials. Materials and method:Thethirty standard aluminum dies were fabricated to receive a full contour IPS e.Max CAD crowns.An impression with two-stage putty-wash impression with spacer technique was taken.The thirty impressions were distributed into three groups;as follows; Group (A) Ten impressions were poured with type IV die stone,Group (B)Ten impressions were poured with type V die stone and Group (C)Tenimpressions were poured with Exacto-form model resin die material.Each die was scanned and IPS e.Max CAD full contour crown was fabricatedusing Sirona CEREC in-Lab CAD/CAM System. Sixteen gap measurements were taken for each sample (Buccal, Mesial, Lingual and Distal), Pre and postcementation process were measured using a digital microscope.The results of this study showed that there and post-cementation procedure.From the results of this study,it could be concluded that the Exacto-form provided the least vertical gap, when used IPS e.Max CAD full contour restorations. Die stone type V could be the next choice, which is preferred over to die stone type IV.cementation step incressed the marginaly